La scrittura scientifica: annotazioni pedagogiche - Franco Cambi (Firenze University Press, 2011)
The passage from orality to writing is a turning point in the culture and its forms, the use of the word, in communication, but also in the same thought. It develops thinking interpretive, reflective, tend to be more general and abstract. But the writing becomes, immediately, the heir of orality, and changes its sign. It fixes it. it submits to the interpretation and variation / specialization, and it gradually becomes clearer and more precisely through the instrument-write. The author studied these topics in educational and he reflects on some aspects of writing as a learning tool.